2015
DOI: 10.1016/j.jpsychires.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Hoarding and emotional reactivity: The link between negative emotional reactions and hoarding symptomatology

Abstract: Hoarding disorder (HD) is characterized by difficulty discarding, clutter, and frequently excessive acquiring. Theories have pointed to intense negative emotional reactions (e.g., sadness) as one factor that may play a critical role in HD’s etiology. Preliminary work with an analogue sample indicated that more intense negative emotions following emotional films were linked with greater hoarding symptoms. Symptom provocation imaging studies with HD patients have also found evidence for excessive activation in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 53 publications
(92 reference statements)
11
32
0
Order By: Relevance
“…Extending prior research on emotional prediction and intensity in HD (Shaw et al, 2015; Timpano et al, 2014), we predicted that:…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Extending prior research on emotional prediction and intensity in HD (Shaw et al, 2015; Timpano et al, 2014), we predicted that:…”
mentioning
confidence: 72%
“…Preliminary research suggests that student volunteers with hoarding symptoms exhibit ER-related problems such as greater intensity of NA and decreased emotion tolerance (Timpano, Shaw, Cougle, & Fitch, 2014). On self-report measures, individuals with HD report difficulty engaging in goal-directed behavior when distressed and difficulty accessing to strategies for regulating emotions (Fernandez de la Cruz et al, 2013), and report anticipating a higher level of NA when discarding (Shaw, Timpano, Steketee, Tolin, & Frost, 2015). …”
mentioning
confidence: 99%
“…Beliefs about the nature of possessions and beliefs about the necessity of maintaining control over possessions, beliefs about responsibility for possessions, and beliefs about the necessity of perfection. Many experimental and observational studies corroborate the observations provided in the Frost and Hartl model of HD and emotional reactivity [13], intolerance of uncertainty [14], anxiety sensitivity [15] and impulsivity [16]. The model has become a basis for classical cognitive-behavioral therapy (CBT) for HD, whose efficacy has been established in clinical trials [17].…”
Section: Mini Reviewmentioning
confidence: 57%
“…Emotional reactivity describes the intensity and duration of emotions an individual experiences following exposure to emotional stimuli [33] and it has been postulated as a possible vulnerability factor for HD. An internet study of individuals who self-reported hoarding symptoms found that individuals with higher levels of emotional reactivity also reported higher levels of hoarding symptom severity [33] .…”
Section: Attachment Beliefs Behaviors and Emotionsmentioning
confidence: 99%
“…An internet study of individuals who self-reported hoarding symptoms found that individuals with higher levels of emotional reactivity also reported higher levels of hoarding symptom severity [33] . The association was strongest in the context of higher levels of fear of making an incorrect decision and lower levels of confidence in the individual's ability to remember information [33] .…”
Section: Attachment Beliefs Behaviors and Emotionsmentioning
confidence: 99%